The Spirituality of Prayer Fellowship: A Theological Study of the Life of the Early Church According to Acts 2:41-47 - Ishak Isai Kaseh (Proskuneo: Journal of Theology, 2026)
The Prayer Fellowship developed in line with the influence of the charismatic movement in Indonesia. The Prayer Fellowship became an integral part of the church that is inseparable from the mainstream Protestant churches such as the Evangelical Christian Church Synod in Timor (GMIT). This study focuses on the Prayer Fellowship within the scope of the GMIT Synod viewed from a biblical perspective. This study is oriented towards the form of early church fellowship implemented by the Prayer Fellowship that the characteristics of the early church are still relevant today. The purpose of this study is to see the relevance of the life of the early church for the growth of the congregation's faith through the Prayer Fellowship. The research method used is a descriptive qualitative approach with the method of biblical exegesis and through literature studies. The author explores the meaning of the text can help provide a good theological understanding of the early church fellowship. The author refers to Dietrich Bonhoeffer's understanding of sanctorum communio providing an understanding of the Prayer Fellowship that brings peace to the world. The result of this study is to provide a theological understanding of the early church fellowship in the text of Acts 2:41-47 which is still relevant to the life of the church today through the Prayer Fellowship within the scope of the GMIT Synod.